Water and nitrogen management influence on oil and protein concentration in maize. (2nd February 2023) - Hammad, Hafiz Mohkum; Abbas, Farhat; Ahmad, Ashfaq; Farhad, Wajid; Wilkerson, Carol Jo; Hoogenboom, Gerrit
Abstract: The effects of water and nitrogen management on the oil and protein concentration of maize ( Zea mays L.) grown in semiarid conditions are not well documented, although it is rather important for local consumers. The objectives of this study were, therefore, to determine the interaction between different nitrogen fertilizer rates and irrigation regimes on nitrogen uptake, and oil and protein content of maize grain. The importance of this study is to understand how the interaction of nitrogen and irrigation management affects the growth of maize and, thus, identify the best management practices to attain an optimal yield. A field experiment was conducted for 2 consecutive years in 2009 and 2010 using 5 nitrogen fertilizer rates, ranging from 100 to 300 kg N ha −1, and 3 levels of irrigation management, ranging from 375 to 525 mm ha −1, for a total of 15 treatments. The results showed that nitrogen accumulation in the maize plant linearly increased in applications up to 300 kg N ha −1 even under deficit irrigation (375 mm ha −1 ). For the application of 300 kg N ha −1 under optimum irrigation (525 mm ha −1 ), nitrogen accumulation in the plant's aboveground canopy was significantly increased (e.g., 145.7 and 144.3 kg ha −1 during 2009 and 2010, respectively) as compared to smaller N application rates. The combined nitrogen and irrigation regimes of 300 kg N ha −1 with 525 mm of irrigation resulted in the numerically maximum grain oil concentration, that is, 62 and 65 g kg −1 during 2009 and 2010, respectively, and protein concentration in grains, that is, 116 and 120 g kg −1 during 2009 and 2010, respectively. The regression analyses showed that the protein and oil concentrations of the grain are significantly and positively correlated with total nitrogen uptake. The nitrogen concentration in maize is driven by irrigation water and nitrogen fertilizer rates. Therefore, irrigation water and nitrogen fertilizers are the major inputs for not only improving maize grain yield but also maize grain quality. Core Ideas: Oil and protein contents of maize grain were significantly correlated with plant nitrogen uptake. Drought stress enhanced nitrogen uptake and assimilation in maize roots. Nitrogen fertilizer has significant interaction with irrigation regimes during maize cultivation.